The technological mediation in the university extension for health promotion - Elena Camilo Parrón; Alberto Pérez Martínez (Centro Provincial de Información de Ciencias Médicas, 2020)
The university extension, as one of the training processes of the universities has great relevance, reason why a critical valuation about it and its manifestation in the Cuban universities is made in this work, particularly with the use of the information and communications technologies for health promotion. It is concluded that the use of these technologies is indispensable to favor the improvement of this process and, specifically in health, they contribute to guarantee a good diagnosis.